A-to-I RNA Editing in Cancer: From Evaluating the Editing Level to Exploring the Editing Effects - Wang, Heming; Chen, Sinuo; Wei, Jiayi; Song, Guangqi; Zhao, Yicheng (Frontiers in Oncology, 2021)
As an important regulatory manner at the post-transcriptional level in metazoans, Adenosine Deaminases that act on RNA proteins (ADARs) induced A-to-I RNA editing modification of double-stranded RNA has been widely detected and reported. Editing may lead to non-synonymous amino acid mutations, RNA secondary structure alteration, pre-mRNA processing changing, and microRNA-mRNA re-direction, thereby affecting multiple cellular processes and functions. In recent years, researchers have successfully developed several bioinformatical software tools and pipelines to identify RNA editing sites. However, there are still no widely accepted editing sites analyzing standards due to a variety of parallel optimization organizing RNA high-seq protocols and programs. It is also a challenging to identify RNA editing by normal protocols for tumor samples due to the high DNA mutation rate. Numerous RNA editing sites have been reported to be located in non-coding regions, and can affect the biosynthesis of ncRNAs, including miRNAs and circular RNAs. Predicting the function of RNA editing located in non-coding regions and ncRNAs are significantly difficult. In this review, we aim to provide a better understanding of bioinformatics strategies for human cancer A-to-I RNA editing identification, and briefly discussing recent advances in related areas such as editing induced oncogene and antioncogene effects.